20. NUTRITION KNOWLEDGE AND NUTRITIONAL STATUS AMONG ETHNIC MINORITY CHILDREN IN TRA VINH PROVINCE (Vietnam Journal of Community Medicine, 2025)
Objective: This study aimed to assess the mean nutrition knowledge score, the proportion of children demonstrating adequate knowledge, and the association between nutrition knowledge and nutritional status among ethnic minority children in Tra Vinh province, Vietnam.Method: A cross-sectional study was conducted in September 2024 involving 714 ethnic minority children aged 5 to 16 years in Tra Vinh province.Results: The mean nutrition knowledge score among participants was 6.7 ± 3.6. The proportions of children with low, moderate, and high knowledge levels were 35.4%, 19.7% and 44.8%, respectively. Boys’ nutrition knowledge score significantly lower than girls (p = 0.01) and children aged 11-16 years scored significantly higher than those aged 5-10 years (p < 0.001). Furthermore, children with normal nutritional status had significantly higher knowledge scores compared to those who were undernourished or overweight/obese (p = 0.013).Conclusion: Nutrition knowledge score among ethnic minority children was moderate, with a considerable proportion exhibiting low levels of correct knowledge. Poor knowledge was particularly prevalent among younger children, boys, and those with malnutrition. Targeted nutrition education interventions are warranted to improve knowledge and promote healthy dietary behaviors in this vulnerable population.
Keywords: Nutrition knowledge; nutritional status; ethnic minority children.